Q. 24.4( 30 Votes )

Verify that a÷(b + c) (a ÷ b)+(a ÷ c) for each of the following values of a, b and c:

(a) a = 12, b = - 4, c = 2

(b) a = ( - 10), b = 1, c = 1

Answer :

(a) It is given in the question that,


a = 12


b = - 4


And,


c = 2


We have to verify: a ÷ (b + c) (a ÷ b) + (a ÷ c)


Now,


a ÷ (b + c)


= 12 ÷ (-4 + 2)


= 12 ÷ (-2)


=


= - 6


Also,


(a ÷ b) + (a ÷ c)


= [12 ÷ (- 4)] + [12 ÷ 2]


= +


= - 3 + 6


= 3


Therefore,


- 6 3


Hence,


a ÷ (b + c) (a ÷ b) + (a ÷ c)


Verified


(b) It is given in the question that,


a = (- 10)


b = 1


And,


c = 1


We have to verify: a ÷ (b + c) (a ÷ b) + (a ÷ c)


Now,


a ÷ (b + c)


= (-10) ÷ (1 + 1)


= (-10) ÷ (2)


=


= - 5


Also,


(a ÷ b) + (a ÷ c)


= [(-10) ÷ 1] + [(-10) ÷ 1]


= +


= - 10 + (- 10)


= - 10 - 10


= - 20


Therefore,


- 5 - 20


Hence,


a ÷ (b + c) (a ÷ b) + (a ÷ c)


Verified

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.